Building a strong brand image: the role of storytelling in marketing - Popo Suryana (SEAN Institute, 2024)
A strong brand image is a strategic key for companies in facing increasingly tight business competition. This research aims to investigate the role of storytelling in building a strong brand image in a marketing context. This research uses a qualitative approach with descriptive methods. The research results show that storytelling has a crucial role in strengthening brand image. First, storytelling is able to create deep emotional bonds between companies and consumers, evoke positive feelings, and stimulate strong emotional responses. It not only presents product information, but also forms an emotional experience that sticks in consumers' memories. Second, storytelling builds close connections between brands and consumers by presenting stories about the company's integrity, goals and vision. This creates closer relationships, strengthens trust, and increases consumer loyalty. Third, storytelling gives a brand a deep dimension and character, forming a unique brand identity and differentiating it from competitors. By detailing the company's unique aspects, values, and history, storytelling creates a lasting impression in the minds of consumers. Overall, storytelling strategies, such as data-driven, philanthropic, and customer-led storytelling, are not only effective marketing tools but also a strong foundation in strengthening and establishing a meaningful brand image.